Are microplastics efficient remediation tools for removing the statin Lipitor? A laboratory experiment with meiobenthic nematodes - Aldraiwish, Bayan M.; Alaqeel, Maha M.; Al-Hoshani, Nawal; Özdemir, Sadin; Pacioglu, Octavian; Necula, Marian; Milea, Eduard C.; Hedfi, Amor; Rudayni, Hassan A.; Boufahja, Fehmi (Frontiers in Marine Science, 2024)
Introduction The current experiment investigated the multifaceted effects induced by microplastics and the statin Lipitor on marine benthic nematodes. Methods The nematodes were exposed to a single polystyrene and polyvinyl chlorides (both at 1 mg.kg-1 Dry Weight) and two Lipitor concentrations (0.1 and 1 mg.l-1), as well as to a mixture of both types of pollutants, for 30 days. Results The results highlighted a significant decrease in the abundance, individual biomass, and diversity of nematodes directly with the addition of polyvinyl chlorides and/or Lipitor. These treatments induced a greater mortality rate among microvores and diatom feeders compared to other feeding types of nematodes. Discussion The nematofauna underwent a strong restructuring phase following exposure to microplastics and Lipitor when added alone, leading to the disappearance of sensitive species and their replacement by more tolerant taxa. The toxicity of Lipitor is attenuated by the physical bonding with polystyrene when added to a mixture and has no negative effect on marine nematode species.